2002
DOI: 10.1021/jm020977+
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Structure−Activity Relationships, and Molecular Modeling Studies of 2,3-Diaryl-1,3-thiazolidin-4-ones as Potent Anti-HIV Agents

Abstract: Starting from 1H,3H-thiazolo[3,4-a]benzimidazoles (TBZs), we performed the design, synthesis, and the structure-activity relationship studies of a series of 2,3-diaryl-1,3-thiazolidin-4-ones. Some derivatives proved to be highly effective in inhibiting HIV-1 replication at nanomolar concentrations with minimal cytotoxicity, thereby acting as nonnucleoside HIV-1 RT inhibitors (NNRTIs). Computational studies were used to delineate the ligand-RT interactions and to probe the binding of the ligands to HIV-1 RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
81
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(83 citation statements)
references
References 9 publications
(15 reference statements)
0
81
0
2
Order By: Relevance
“…4-Thiazolidone derivatives have attracted continuing interest over the years because of their diverse biological activities including anti HIV activity. [3][4][5][6][7][8][9] these derivatives acts on HIV-1 reverse transcriptase (HIV-1 RT) enzyme. RT inhibitors are of two types: nucleoside reverse transcriptase inhibitors (NRTIs), which act as chain terminators to block the elongation of the HIV-1 viral DNA strand, and non-nucleoside reverse transcriptase inhibitors (NNRTIs), which directly inhibit RT enzyme by binding to the allosteric site near the polymerase active site.…”
Section: Introductionmentioning
confidence: 99%
“…4-Thiazolidone derivatives have attracted continuing interest over the years because of their diverse biological activities including anti HIV activity. [3][4][5][6][7][8][9] these derivatives acts on HIV-1 reverse transcriptase (HIV-1 RT) enzyme. RT inhibitors are of two types: nucleoside reverse transcriptase inhibitors (NRTIs), which act as chain terminators to block the elongation of the HIV-1 viral DNA strand, and non-nucleoside reverse transcriptase inhibitors (NNRTIs), which directly inhibit RT enzyme by binding to the allosteric site near the polymerase active site.…”
Section: Introductionmentioning
confidence: 99%
“…It needs to be accounted to show different physiological activities. They found uses as antitubercular [3], antimicrobial [4][5][6][7][8], antiinflammatory [9], anticancer [10], antihistamines [11], anticonvulsant [12] and as antiviral agents especially as anti-HIV agents [11,13,14]. It has been extensively reported that the antibacterial activity strongly depended on the nature of substituents at C2 and N3 of thiazolidinone ring.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 NNRTIs bind in a noncompetetive way to a unique region on the enzyme, namely nonsubstrate-binding site, resulting in alteration of its function and therefore achieving supression of HIV-1 replication with high selectivity. 9 Although combined use of nucleoside inhibitors of RT (NRTIs), non-nucleoside RT inhibitors (NNRTIs) and protease inhibitors (PIs) in the treatment of HIV infections may provide a dramatic recovery in most HIV-infected persons, resistance to the currently used agents remains as a clinical problem. 5 Consequenlty, there is still a need for novel and safe antiviral agents with potent and selective action which are also effective against mutant strains of HIV.…”
Section: Introductionmentioning
confidence: 99%